An assessment of racial differences in the upper limits of normal ALT levels in children and the effect of obesity on elevated values. Issue 5 (30th May 2016) - Kliethermes, S.; Ma, M.; Purtell, C.; Balasubramanian, N.; Gonzalez, B.; Layden, T. J.; Cotler, S. J.
Summary: Objectives: Childhood obesity is a risk factor for non‐alcoholic fatty liver disease and poses important public health issues for children. Racial differences in alanine aminotransferase (ALT) levels among children have not been described. This study aimed to identify racial differences in upper limit normal (ULN) ALT levels and evaluate the effect of obesity on elevated levels in children without other metabolic risk factors. Methods: National Health and Nutrition Examination Surveys and clinical data from the Loyola University Health System were used to determine ULN ALT by race and gender. Quantile regression was used to evaluate the impact of obesity on elevated ALT and to identify potential risk factors for ALT above the ULN. Results: Upper limit normal (ULN) ALT was approximately 28.0 and 21.0–24.0 U/L for boys and girls, respectively. No significant difference in ULN ALT across race was observed. Obesity was significantly associated with elevated ALT; obese children with elevated ALT had values 10 U/L higher than normal‐weight children. Conclusions: Racial differences in ALT levels among adults are not evident in children. Obesity, in the absence of metabolic risk factors and other causes of liver disease, is associated with elevated ALT, providing evidence against the concept of healthy obesity in children.